Imputação objetiva nos crimes contra o Sistema Financeiro Nacional: parâmetros de identificação do risco permitido segundo as diretrizes do Mercado Financeiro - Moraes, Jenifer da Silva (2020)
This paper seeks to achieve a dogmatic approach about the Law of Crimes Against the National Financial System and the Financial Market. Since the enactment of Law 7,492 / 86, there have been several problems faced by law enforcement officials in order to instrumentalize the law as a real instrument of protection of the Financial System. Among the observed problems, we have as main the irreconcilable dissent in relation to the legal good protected by the types of Law nº 7,492 / 86 and a general disregard of the administrative regulation of the National Financial System. Therefore, the study aims, fundamentally, to evaluate if the administrative legislation can be an adequate parameter for the identification of the risk allowed in the National Financial System according to the guiding parameters of the Objective Imputation theory. With this, the aim is to bring the application of legislation closer to the system that it aims to protect and legitimize the social function that essentially belongs to Legal Dogmatics. The chosen path to resolve the issue will be, first, the examination of Law No. 7,492 / 86 by doctrine and jurisprudence. Subsequently, the effectiveness of Criminal Dogmatics in solving the problems identified in the first chapter will be analyzed, as well as a study on the legal property protected in crimes against the National Financial System. Afterwards, the historical evolution of the objective imputation theory will be studied, as well as its main aspects, with emphasis on the concept of Forbidden Risk. Finally, the main risks that permeate the financial market for overlapping administrative parameters with criminal concepts will be analyzed